THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND PREMENOPAUSE SYMPTOMS IN WOMEN AGED 40-49 - Siti Lestari; Redha Ulfa; Reni Hariyanti; Elvi Febria Marnita; Srianty Siregar; Fika Lestari; Siska Desta Roza (Journal of Maternity Care and Reproductive Health, 2026)
Premenopausal syndrome is a symptom that is felt both physically and psychologically when entering menopause. Objective: To identify the relationship between physical activity and premenopausal symptoms in women aged 40-49 years in the work area of Pelayang Jambi village. Method: This study used a correlation analytic design with a cross-sectional approach model. The number of samples was 103 respondents with a stratified proportional random sampling method. Data collection used the IPAQ and MRS questionnaires, data analysis used the Spearman-rho test. Results: Showed that most respondents had moderate physical activity 51 (49.5%) and most respondents experienced premenopausal symptoms in the mild symptom category 40 (38.8%). There was a relationship between physical activity and premenopausal symptoms with a p value of 0.01 (p <0.05). Conclusion: The higher the physical activity, the more severe the premenopausal symptoms felt. Premenopausal symptoms in women can be reduced by physical activity in the form of a leisurely walk every day for 15 minutes or low-impact aerobic exercise three to five times per week